Origanum majorana Extracts: A Preliminary Comparative Study on Phytochemical Profiles and Bioactive Properties of Valuable Fraction and By-Product - Simone Bianchi; Rosaria Acquaviva; Claudia Di Giacomo; Laura Siracusa; Leeyah Issop-Merlen; Roberto Motterlini; Roberta Foresti; Donata Condorelli; Giuseppe Antonio Malfa (Plants)
Origanum majorana L. (O. majorana) (Lamiaceae) is an aromatic Mediterranean plant widely used in food, cosmetics, and traditional medicine due to its aroma and rich content of bioactive compounds. While its leaves and flowers are commonly utilized, lignified stems are often discarded. This study compared hydroalcoholic extracts from the leaves and flowers (valuable fraction, VF) and stems (by-product, BP). Phytochemical analysis revealed qualitatively similar profiles, identifying 20 phenolic compounds, with Rosmarinic acid and Salvianolic acid B as the most and second most abundant, respectively. Antioxidant activity was evaluated in vitro using DPPH (IC50 [µg/mL]: VF 30.11 ± 3.46; BP 31.72 ± 1.46), H2O2 (IC50 [µg/mL]: VF 103.09 ± 4.97; BP 119.55 ± 10.58), and O2•− (IC50 [µg/mL]: VF 0.71 ± 0.062; BP 0.79 ± 0.070). Both extracts (20 µg/mL) fully restored oxidative balance in hemin-stressed AC16 cardiomyocytes, without altering the expression of catalase, heme-oxygenase 1, superoxide dismutase 2, or ferritin. Anti-inflammatory activity in LPS-stimulated RAW 264.7 macrophages showed that VF (IC50 400 µg/mL) reduced •NO release to control levels, while BP achieved a ~60% reduction. Cytotoxicity was assessed on cancer cell lines: CaCo-2 (IC50 [µg/mL]: VF 154.1 ± 6.22; BP 305.2 ± 15.94), MCF-7 (IC50 [µg/mL]: VF 624.6 ± 10.27; BP 917.9 ± 9.87), and A549 (IC50 [µg/mL]: VF 720.8 ± 13.66; BP 920.2 ± 16.79), with no cytotoxicity on normal fibroblasts HFF-1 (IC50 > 1000 µg/mL for both extracts). Finally, both extracts slightly inhibited only CYP1A2 (IC50 [µg/mL]: VF 497.45 ± 9.64; BP 719.72 ± 11.37) and CYP2D6 (IC50 [µg/mL]: VF 637.15 ± 14.78, BP 588.70 ± 11.01). These results support the potential reuse of O. majorana stems as a sustainable source of bioactive compounds for nutraceutical and health-related applications.